New ways to admire zebrafish: progress in functional genomics research methodology - Cathleen Teh; Serguei Parinov; Vladimir Korzh (BioTechniques, 2005)
The main challenge of the post-genomic era is to functionally characterize genes identified by the genome sequencing projects. Model organisms, including zebrafish, are indispensable for this demanding task. Zebrafish has been successfully incorporated into large-scale genetic screens due to the optical clarity of the embryos and their accessibility to various experimental techniques throughout development. The attractiveness of the zebrafish as a model organism is enhanced by the availability of continuously improving genomic tools and methodologies for functional characterization of the gene. This article will highlight the current techniques used in the field, with the focus on transgenesis.